Analisis Kelayakan Usaha UMKM Pada Ayam Geprek Griya Dhaharan Jember - Dea Azzahrotu Dinji; Nurlaila Mansur; Samuel Rizal; Meilinda Maulidya Widiyanti; Selvi Putri Rahayu Bambang Hartono; Ana Rosalia; Eka Denta Permana; Aisyah Nurul Umamah; Oryza Ardhiarisca; Avisenna Harkat (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to analyze the business feasibility of the Ayam Geprek Griya Dhaharan MSME in Jember Regency, reviewed from several aspects: market, financial, technical/operational, management and organization, economic and social, and environmental impact. This research uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The results show that from the market aspect, the business has stable demand with affordable prices and unique products. From the financial aspect, BEP analysis shows that the break-even point is only 368 portions/month, far below actual production capacity; Payback Period of ±15 days; NPV of Rp641,359,717 (positive); and IRR of 177.12%, far exceeding the discount rate of 12%. From the technical aspect, the supply chain and production process are adequate. Management has a clear division of tasks. From the economic and social aspects, the business contributes to job creation and local economic activity. From the environmental aspect, waste generated is minimal and does not cause significant disturbance. Overall, the Ayam Geprek Griya Dhaharan business is declared feasible to run and develop.